Frequency of irrigation with saline water in sugar-apple seedlings produced on substrate with polymer - Silva, Aldeir R.; Bezerra, Francisco T. C.; Cavalcante, Lourival F.; Pereira, Walter E.; Araujo, Leandro M. [UNESP]; Bezerra, Marlene A. F. (Univ Federal Campina Grande, 2018)
The objective of this work was to evaluate the growth of sugar-apple seedlings under irrigation management with saline water in a substrate with soil amendment. Treatments were obtained from the arrangement between polymer doses (0, 0.2, 0.6, 1.0 and 1.2 g dm(-3)) and levels of irrigation water electrical conductivity (0.3, 1.1, 2.7, 4.3 and 5.0 dS m(-1)), associated with irrigation frequencies (daily and every alternate day), and two additional treatments to evaluate container volume (1.30 and 0.75 dm(3)), using a randomized complete block design, with four replicates. At 120 days after sowing, the variables substrate salinity, stem diameter, plant height, number of leaves and Dickson quality index were determined. Data were submitted to analyses of variance, regression and contrast. Substrate salinity increased with the increase in irrigation water electrical conductivity and polymer doses. Growth and quality of the seedlings were reduced with increasing irrigation water salinity, and highest values of the variables were obtained in seedlings under daily irrigation. Container with larger volume led to higher growth. The use of hydrated polymer at the adopted levels had no effect on growth and quality of seedlings, requiring further studies. To produce sugar-apple seedlings with better quality, irrigation frequency should be daily and water electrical conductivity should be lower than 2 dS m(-1).
Keywords: Annona squamosa; soil amendment; container volume; seedling quality